Health Risk Behaviors of Employees in Selected Oil Servicing Companies in Port Harcourt - Imiete Godspower; Kpang Meelu-Bari Barinua Tsaro (Occupational Health and Safety Society of Nepal, 2019)
Background: The recent rate of deaths of worker in the oil industry is alarming. However, the way managers of the workers handle the problem is even more worrisome. This study investigated the health risk behaviours of employees in selected oil servicing companies in Port Harcourt city, Nigeria. Methodology: The study adopted the purposive sampling technique to select three notable oil servicing firms in the area and then selected 175 workers of the 350 workers as target population. Questionnaires were used to elicit information regarding the subject matters from the respondents. Data generated were presented in tables, while percentages were used as a yardstick for conclusions. Results: Findings showed that most of the respondents exceeded driving speed limit (73.6%), do not get enough rest (84.9%), alcohol consumption (76.1%), cannot manage their individual stress (75.9%), having more than one sexual partners (74.8%). Also noted in the study is that most workers do not maintain low sugar diet (65.6%), do not take adequate fruits/vegetables (54.1%), do not get adequate sleep (54.6%), regular exposure to sun (58.5%), not coping with work stress (59.2%) and not socializing with friends (56%). Conclusions: The exposition revealed that as a result of work demand oil company workers in the study area engage in poor life styles that are risky to health. Therefore, there is need to synchronise the work demand and the life style of workers in a way that, work that is supposed to give a better life to workers does not kill them instead.